Amazing grace [videorecording (DVD)] - Mannes, Elena; Moyers, Bill D. (Athena, 2011)
Bill Moyers tells the story of this song, one of the most popular pieces of music in the English language, through the people who have sung it. He also tells the story of John Newton, once the captain of an English slave ship, who came to faith after surviving a storm at sea in the eighteenth century and wrote the lyrics which across distances of time and culture have become, when set to music, a courier of the spirit to millions of people.